2018
DOI: 10.1021/acsami.8b08471
|View full text |Cite
|
Sign up to set email alerts
|

Supported Two-Dimensional Materials under Ion Irradiation: The Substrate Governs Defect Production

Abstract: Focused ion beams perfectly suit for patterning two-dimensional (2D) materials, but the optimization of irradiation parameters requires full microscopic understanding of defect production mechanisms. In contrast to freestanding 2D systems, the details of damage creation in supported 2D materials are not fully understood, whereas the majority of experiments have been carried out for 2D targets deposited on substrates. Here, we suggest a universal and computationally efficient scheme to model the irradiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 52 publications
12
98
0
Order By: Relevance
“…In addition, the formation thresholds for Mo-vacancy and DIV are not very high (18-29 eV). Kretschmer et al [168] combined analytical potential molecular dynamics with Monte Carlo simulations to simulate helium and neon ion irradiation of MoS 2 nanosheets deposited on SiO 2 substrates. Their simulation indicated that substrates governed the defect production of irradiated MoS 2 layers.…”
Section: Irradiation Mechanism and Theoretical Simulationsmentioning
confidence: 99%
“…In addition, the formation thresholds for Mo-vacancy and DIV are not very high (18-29 eV). Kretschmer et al [168] combined analytical potential molecular dynamics with Monte Carlo simulations to simulate helium and neon ion irradiation of MoS 2 nanosheets deposited on SiO 2 substrates. Their simulation indicated that substrates governed the defect production of irradiated MoS 2 layers.…”
Section: Irradiation Mechanism and Theoretical Simulationsmentioning
confidence: 99%
“…[15,16] More recently, FIB irradiation has been extended as a means of structural modification and nanopatterning in 2D materials such as graphene. [17] Theoretical studies [18][19][20][21] on the role of ion incidence angle and substrate effects in the defect creation process in 2D materials like TMDs and graphene, and similar experimental studies, [8,22,23] are starting to emerge. A wide range of techniques for defect creation have been reported in literature including plasma etching, [24] thermal decomposition, [25] acid etching, [26,27] electron irradiation, [28] and ion irradiation.…”
mentioning
confidence: 99%
“…[8] As of now, there is a relatively poor correspondence between ion irradiation experiments and theory in 2D materials. [8,9,18,19,31] One likely reason for these discrepancies is the inadequate understanding of experimental parameters. For example, material contamination has been ubiquitously reported after ion irradiation and while it plays a significant role in analytical and structural characterization, such "substrates" are rarely accounted for in theoretical simulations.…”
mentioning
confidence: 99%
“…For a given delivered dose, the ion beam provides a high concentration of effective adsorption sites for atmospheric p-dopants (or adventitious hydrocarbons) within the area defined by the spread of the Gaussian probe extension. The probe has spatially trailing lower-dose tails, the damage of which extends to more than 10 nm and may induce additional n-doping with no complementary adsorbant saturation, i.e., by creating unsaturated SVs in the bottom sulfuric layer [34,39]. A larger irradiation area will thus provide more effective p-doping sites while stifling the n-doping response as the probe tails begin to extend past the FET channel.…”
Section: Resultsmentioning
confidence: 99%